2022
DOI: 10.1111/tpj.15878
|View full text |Cite
|
Sign up to set email alerts
|

Variation on a theme: the structures and biosynthesis of specialized fatty acid natural products in plants

Abstract: SUMMARY Plants are able to construct lineage‐specific natural products from a wide array of their core metabolic pathways. Considerable progress has been made toward documenting and understanding, for example, phenylpropanoid natural products derived from phosphoenolpyruvate via the shikimate pathway, terpenoid compounds built using isopentyl pyrophosphate, and alkaloids generated by the extensive modification of amino acids. By comparison, natural products derived from fatty acids have received little attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 119 publications
(143 reference statements)
0
9
0
Order By: Relevance
“…Very long-chain fatty acids (VLCFAs) are molecules with a hydrocarbon chain containing more than 18 carbon atoms, which are important components of plant cell membrane lipids, cutin wax, and seed storage lipids ( Scott et al., 2022 ). VLCFAs and their derivatives play an important role in plant growth and development, signal transduction, and adverse stress.…”
Section: Introductionmentioning
confidence: 99%
“…Very long-chain fatty acids (VLCFAs) are molecules with a hydrocarbon chain containing more than 18 carbon atoms, which are important components of plant cell membrane lipids, cutin wax, and seed storage lipids ( Scott et al., 2022 ). VLCFAs and their derivatives play an important role in plant growth and development, signal transduction, and adverse stress.…”
Section: Introductionmentioning
confidence: 99%
“…VLCFAs and their derivatives, including alkanes, ketones, alcohols, aldehydes, and wax esters, are the main components of cuticular wax. Thus, their content and composition are tightly associated with plant growth, development, and stress tolerance capability ( Haslam and Kunst, 2013 ; Scott et al., 2022 ). In Arabidopsis, drought, salt and abscisic acid stress treatments lead to a significant increase in the amount of leaf cuticular wax ( Kosma et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…composition are tightly associated with plant growth, development, stress tolerance capability (Haslam and Kunst, 2013;Scott et al, 2022). In Arabidopsis, drought, salt and abscisic acid stress treatments lead to a significant increase in the amount of leaf cuticular wax (Kosma et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the three biosynthetic pathways for PAs proposed in plants, the crepenynate pathway has been deemed to be a major one, and found only in campanulids, which gives rise to the majority of the known PAs [3,7]. Previous studies suggested that Fatty Acid Desaturase 2 (FAD2) [8] plays important roles in the initiation of PA biosynthesis in all lineages of campanulids investigated so far [9,10,11,12]. FAD2 is a member of the fatty acids desaturases family, usually catalyzes desaturation at the C-12 position (i.e., Δ 12 , this notation is used consistently throughout) of oleic acid to form linoleic acid on the endoplasmic reticulum [13].…”
Section: Introductionmentioning
confidence: 99%